Food-Level Analysis to Identify Dietary Choices With the Highest Nutritional Quality and Lowest Greenhouse Gas Emissions and Price - Aceves-Martins, Magaly; Bates, Ruth L.; Craig, Leone C. A.; Chalmers, Neil; Horgan, Graham; Boskamp, Bram; de Roos, Baukje (Frontiers in Nutrition, 2022)
Introduction: Food systems are challenged to provide healthy, sustainable and affordable foods. From a consumer perspective, identifying healthy, sustainable and affordable choices based on individual food products rather than diets could promote better shopping choices. Objective: To identify foods and drinks with the highest nutritional quality and lowest cost and environmental impact. We also assessed how a combination of these indicators (e.g., nutritional quality, greenhouse gas emissions (GHGE) and cost) for food categories aligned with current UK dietary recommendations. Materials and Methods: We performed a secondary analysis of the National Diet and Nutrition Survey (NDNS) nutrient databank year 11 (2018/2019). Spearman correlation coefficients were used to assess the strength of relationships between nutritional quality, costs and environmental impact per 100 kcal. In addition, we developed an optimised nutritional quality, GHGE and cost score for each food or drink item based on the overall medians for each of these indicators. Results: Median nutritional value was highest for fruit and vegetables, whilst median GHGE and cost was lowest for starchy carbohydrates, fats and items of which consumption should be limited. The relative proportions of foods considered the most nutritious, environmentally sustainable and at lower cost in each of the food categories, on a per 100 kcal basis, were comparable to the proportions in the Eatwell Guide, except for the proportion of fruits and vegetables being smaller and the proportion of potatoes, bread, rice, pasta, and other starchy carbohydrates being larger in our analysis. Conclusions: Public health efforts should consider the impact of dietary choices not only in terms of nutritional quality but also in terms of cost and environmental impact. Our food-based analysis shows a large variation in nutritional quality, GHGE and cost within and across food categories, which may provide consumers with opportunities for "food swaps" that are more nutritious and have a lower cost and environmental impact.